PERKEMBANGAN KARIR KARYAWAN DI PDAM TIRTA MOEDAL SEMARANG - Ninik Dwi Rahayu, 13.05.51.0035 (Students' Journal of Economic and Management, 2017)
Employee career development is important for organizations as well as for individuals, But not necessarily every organization has done it. As is the case that happened in PDAM Tirta Moedal Semarang. As a company should be able to develop career employees well, but the fact of career development incompany is not as expected. The purpose of this research is (1) to know career development in PDAM. (2) to know the factors influencing career development in PDAM. (3) to find out the dominant factors influencing employee career development in PDAM. The population of 494 employees. The sample was taken based on the needs of the tool and the homogeneity of the respondents with the number of 100 respondents, Taken with nonprobability sampling method. While the data collection is done by spreading the questionnaire. Data analysis used include descriptive analysis, validity test with factor analysis, reability test with cronbach alpha and analysis multiple regression. The results of this study indicate that career management and career planning have a positive and significant impact on career development. Keywords: Career Management, Career Planning and Career Development.